2007
DOI: 10.1097/jom.0b013e31802ec68c
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Rate Trends in U.S. Occupational Groups: The 1987 to 2004 National Health Interview Survey

Abstract: Development of effective smoking prevention strategies specifically targeting blue-collar groups is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
86
4
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 17 publications
(17 reference statements)
8
86
4
3
Order By: Relevance
“…Interestingly, the authors found that among whites, the differences in smoking rates between white to blue collar workers (21% versus 39%) was a little wider than the differences between blacks (19% versus 28%) 75) . The most recent national data on US smoking rates by occupation appears to have been published by Lee and colleagues in 2007 76) . In their analysis of the 1987-94 and 1997-04 National Health Interview Survey data sets, the authors reported two interesting trends.…”
Section: Tobacco Smoking By Occupation In the United Statesmentioning
confidence: 99%
“…Interestingly, the authors found that among whites, the differences in smoking rates between white to blue collar workers (21% versus 39%) was a little wider than the differences between blacks (19% versus 28%) 75) . The most recent national data on US smoking rates by occupation appears to have been published by Lee and colleagues in 2007 76) . In their analysis of the 1987-94 and 1997-04 National Health Interview Survey data sets, the authors reported two interesting trends.…”
Section: Tobacco Smoking By Occupation In the United Statesmentioning
confidence: 99%
“…According to that study, the smoking rate in Australia gradually decreased over time but blue collar workers still had a higher smoking rate than white collar workers; for example, the professionals group presented the lowest smoking rate, while the cleaners and construction workers group had the highest rate. In the United States, the smoking rate was also higher in blue collar workers than white collar workers, and this pattern was continuously maintained 20) . These findings suggest that low socioeconomic position (SEP), such as manual workers, may be associated with greater smoking rates than high SEP, such as white collar workers.…”
Section: Discussionmentioning
confidence: 95%
“…In the United States, the smoking rate in agricultural workers was 32.5% in 1987−1994 and 29.6% in 1997−2004, respectively. This occupational group had a higher smoking rate than other occupational groups (in all workers: 27.8% in 1987−1994 and 24.5% in 1997−2004, respectively) 20) . This is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations